PENGARUH KEKUASAAN DAN PENGAMBILAN KEPUTUSAN TERHADAP KOMITMEN ORGANISASI GURU SEKOLAH DASAR BPK PENABUR DI JAKARTA - Dian Nataly Paramaartha (Universitas Negeri Jakarta, 2015)
The research objective is to understand comprehensively the effect of power and decision making on teacher’s organizational commitment in BPK PENABUR Primary School in Jakarta. The research methodology is a survey method to form the causal path analysis. Research based on BPK PENABUR’s primary school teacher with total sample 178 teachers. The research on the analysis conclude that (1) power has positive influence on organizational commitment, (2) decision making has positive influence on organizational commitment, and (3) power has positive influence on decision making.